THE IMPACT OF MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. SAMUDERA JAYA SHIPPING - Putra Afriansyah Chatra (Asosiasi Dosen Muda Indonesia, 2024)
This research is a descriptive qualitative research. This research is intended to obtain empirical evidence to test and analyze the performance of human resources at PT. Samudra Jaya Shipping The author determines that the method used is through the survey method and going directly to the field of work. The survey method used is in the mechanical section with a total of around 37 people, data taken from the results of the survey and data collection conducted by the author at the company PT. Samudra Jaya Shipping. The results of the study are simultaneously, motivation and job satisfaction affect employee performance So there is no influence between motivation and employee performance. So there is an influence between job satisfaction and employee performance.